Implementasi Kepatuhan Iran terhadap Protokol Montreal melalui Program HCFC Phase-Out Management Plan (HPMP) Tahun 2017-2021 - Hamidah, St. Nurul; Trisnaningtyas, Januari Pratama Nurratri (University of Jember, 2023)
The Montreal Protocol is an International Environmental Agreement that regulates the protection of the ozone layer by controlling the use of Ozone Depleting Substances (ODS). HCFC is type of ODS which is regulated under the Annex C of the protocol and must be phased-out by parties. Iran is one of the countries that ratified the Montreal Protocol and is obliged to comply with the implementation of the agreement. However, Iran's consumption of HCFCs is reasonably high, resulting a very significant increase in air temperature. This study aims to answer the question on how to implement Iran's compliance with the Montreal Protocol in reducing HCFC consumption. The theory used in this research is the compliance theory by Ronald B. Mitchell to analyze Iran's compliance with the protocol through 3 indicators namely, output, outcome, and impact. This is descriptive qualitative reseacrh with data obtained from literature study. This research results that changes in Iranian behavior are well achieved through the implementation of the HCFC Phase-out Management Plan program. The behavior changes emerged since HPMP involves 4 main areas specifically, training, HCFC conversion, awareness raising, and financial assistance.